Era uma vez, era outra vez... a experiência de multiplicidade no cinema contemporâneo - Pedrosa, Leonardo Bomfim (2022)
The thesis Once upon a time, twice upon a time... The experience of multiplicity in contemporary cinema investigates the recurrence of narrative reboots in films produced after the centenary of cinema that provoke a similar concern: is it possible that the same world exist in a different way? Structured from the methodological configuration of Alain Badiou (2002), the research explores the existing dialogues between a virtually infinite complex of works, which comprises titles belonging to different cinematographies, to understand how the singularity of the contemporary approach around the movement from the one to the multiple takes place. In three chapters of analysis, we seek to understand how the experience of multiplicity is manifested in different categories: 1) the Sherazadian impulse – related to the narrative surplus. 2) the metamorphoses – related to the moment when the reboot takes place along the projection. 3) the evocation of the idea of one over the other – related to the retun of images that suggest the existence of a comparison between different narratives in the womb of the same film.